The social media scale for depression in adolescence - Eve Twivy; Daniel Freeman; Ciorsdan Anderson; Bao Sheng Loe; Felicity Waite (International Journal of Adolescence and Youth)
Social media forms a significant part of adolescents’ lives, yet its impact on depression is unclear. We aimed to develop a questionnaire assessing different ways of using social media, and use it to understand potential associations with depression in adolescence. One thousand one hundred and forty adolescents completed an item pool. Factor analyses were conducted to derive the Social Media Scale (SMS). Ant Colony Optimization was used to develop a short-form SMS containing the factors which uniquely predicted depression as determined by structural equation modelling. The 45-item, nine-factor, SMS, had an acceptable model fit. Five factors (Social comparison; Passing time; Hostility from others; Hostility towards others; and Seeking support) uniquely contributed to depression and together explained 44% of its variance. These factors formed a 15-item short-form SMS, which had an excellent model fit. Social comparison and Passing time on social media had the strongest associations with depression and may be targets for future psychological interventions.